2014
DOI: 10.1097/sap.0b013e318268a803
|View full text |Cite
|
Sign up to set email alerts
|

Transfusions in Autologous Breast Reconstructions

Abstract: Prognostic/risk category, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…As noted above, most authors have found a correlation between the occurrence of postoperative complications or reconstructive failure and the giving of transfusions during the perioperative period [4,5,[17][18][19][20][21][22]24]. Other variables related to transfusion that have demonstrated an ability to influence the appearance of postoperative complications are the number of transfused concentrates [18] and the period of storage of blood prior to transfusion [23].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As noted above, most authors have found a correlation between the occurrence of postoperative complications or reconstructive failure and the giving of transfusions during the perioperative period [4,5,[17][18][19][20][21][22]24]. Other variables related to transfusion that have demonstrated an ability to influence the appearance of postoperative complications are the number of transfused concentrates [18] and the period of storage of blood prior to transfusion [23].…”
Section: Discussionmentioning
confidence: 97%
“…The totality of these findings indicates that there is a relationship between transfusion and complications. The majority of authors coincide in pointing out how transfusion during the perioperative period of microsurgery with free flaps increases the risk of medical or surgical complications and increases the duration of the hospital stay and the percentage of failure of the reconstructive procedure [4,5,[17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting hematoma can compromise flap perfusion by an increased pressure on the microvascular pedicle or directly on the microvascular architecture of the flap. Also, such a bleeding often requires surgical re-exploration and the transfusion of blood products, which is associated with increased morbidity and cost and can further deteriorate the outcome of free tissue transfer [7], [8]. Therefore, the early identification of such patients as well as an early and targeted intervention seems desirable.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, postoperative bleeding can lead to hematoma formation, potentially compromising flap perfusion as well as necessitating the transfusion of blood products, which can further worsen outcomes [7], [8], [9]. Most of the available literature regarding the influence of coagulation on microvascular thrombosis and hematoma formation is based on the identification of preoperative markers [2], [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation